2004
DOI: 10.1007/978-1-4020-2797-0_1
|View full text |Cite
|
Sign up to set email alerts
|

Accreditation in the Framework of Evaluation Activities: A Comparative Study in the European Higher Education Area

Abstract: Higher education systems in Europe are currently undergoing deep reforms. These reforms are triggered by national developments, as well as by the aim to evolve towards comparable systems and ensure the quality of the higher education systems in Europe (Bologna Process). This study was initiated by the education trade unions' goal to widen the scope of the debate on accreditation and evaluation activities in higher education in Europe from a comparative perspective. In order to provide the factual base for this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 28 publications
0
71
0
1
Order By: Relevance
“…The successfully certified entity (e.g., a programme provider in the field of business administration) receives a seal of approval-and from time to time has to undergo a reaccreditation process. Although there are cross-country differences with regard to the practices of accreditation bodies (Eaton 2003;Schwarz and Westerheijden 2004), all accreditors basically do the same: "[A]ccrediting is the process whereby an organization or agency recognizes a college or university or a programme of study as having met certain pre-determined qualifications or standards" (Selden 1960, p. 6). …”
Section: Private Third-party Certificationmentioning
confidence: 98%
See 1 more Smart Citation
“…The successfully certified entity (e.g., a programme provider in the field of business administration) receives a seal of approval-and from time to time has to undergo a reaccreditation process. Although there are cross-country differences with regard to the practices of accreditation bodies (Eaton 2003;Schwarz and Westerheijden 2004), all accreditors basically do the same: "[A]ccrediting is the process whereby an organization or agency recognizes a college or university or a programme of study as having met certain pre-determined qualifications or standards" (Selden 1960, p. 6). …”
Section: Private Third-party Certificationmentioning
confidence: 98%
“…With regard to the governmental student protection via supply regulation, in many countries around the world, it can be observed that governmental authorities for the purpose of preventive consumer protection regulate and control the market entry of private and public providers of higher educational services (see, e.g., Knight and De Wit 1999;Eaton 2003;Schwarz and Westerheijden 2004). The granting of a license which allows a programme provider to legally operate an academic programme in the respective jurisdiction usually is linked to the fulfilment of a set of state-defined minimum quality standards or the demonstration of a successful accreditation by a (non-) governmental accreditation agency.…”
Section: Supply Regulationmentioning
confidence: 99%
“…Formation of the system of views on modern management of HEI takes place on the basis of a large number of studies of scientists and experts in various areas of management and marketing, such as [6,7] and others.…”
Section: о N I F a T O V Amentioning
confidence: 99%
“…CAS is a consortium of forty professional organizations which has developed standards for forty-four functional areas. According to the CAS website, founded in 1979, the Council for the Advancement of Standards in Higher Education (CAS) [14] is the pre-eminent force for promoting standards in student affairs, student services, and student development programs. CAS creates and delivers dynamic, credible standards, guidelines, and Self-Assessment Guides that are designed to lead to a host of quality programs and services.…”
Section: Regional Accreditationmentioning
confidence: 99%
“…In Europe, the primary emphasis on increasing accreditation rigor has come from the various central governments and from the universities themselves [13] [14]. Nevertheless, accordingly to Vėbra and Scheuthle "While the Bologna Process stands for the European Higher Education Area, the European Standards and Guidelines (ESG) and the European Quality Assurance Register (EQAR) are its equivalent for quality assurance [5].…”
Section: Introductionmentioning
confidence: 99%